2014
DOI: 10.1038/cddis.2014.539
|View full text |Cite
|
Sign up to set email alerts
|

An activated unfolded protein response promotes retinal degeneration and triggers an inflammatory response in the mouse retina

Abstract: Recent studies on the endoplasmic reticulum stress have shown that the unfolded protein response (UPR) is involved in the pathogenesis of inherited retinal degeneration caused by mutant rhodopsin. However, the main question of whether UPR activation actually triggers retinal degeneration remains to be addressed. Thus, in this study, we created a mouse model for retinal degeneration caused by a persistently activated UPR to assess the physiological and morphological parameters associated with this disease state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 38 publications
2
64
0
1
Order By: Relevance
“…However, when UPR cannot alleviate ER stress by self-regulation, pro-apoptotic mechanisms play the predominant role, which causes apoptosis of cells. (34,35) The present study found that a sustained dose of SFN significantly down-regulated the protein expression of GRP78/BiP in ER in rd10 retina, suggesting that SFN may inhibit ER stress and thereby reduce photoreceptor apoptosis. The data of this study confirm the protective effect of SFN in a relatively early stage of an RP mouse model.…”
Section: Discussionsupporting
confidence: 56%
“…However, when UPR cannot alleviate ER stress by self-regulation, pro-apoptotic mechanisms play the predominant role, which causes apoptosis of cells. (34,35) The present study found that a sustained dose of SFN significantly down-regulated the protein expression of GRP78/BiP in ER in rd10 retina, suggesting that SFN may inhibit ER stress and thereby reduce photoreceptor apoptosis. The data of this study confirm the protective effect of SFN in a relatively early stage of an RP mouse model.…”
Section: Discussionsupporting
confidence: 56%
“…Saline containing 3% dimethylsulfoxide or DFP solution containing 3% dimethylsulfoxide was injected to the contralateral eye. The final dose of tunicamycin, which was determined according to previous reports, [6][7][8][9] was 300 nmol/eye. The final dose of DFP was 0.5 nmol/eye or 5 nmol/eye.…”
Section: Methodsmentioning
confidence: 99%
“…4,5) The intravitreal tunicamycin injection model is used for an animal model of photoreceptor-specific degeneration. [6][7][8][9] Increase of reactive oxygen species (ROS) is also known to cause ER stress, Parkinson's disease, [10][11][12] Alzheimer's disease, [11][12][13] and photoreceptor degeneration. 14) These ROS are believed to be generated at least in part by Fenton reaction, producing hydroxyl radical from hydrogen peroxide.…”
mentioning
confidence: 99%
“…Nuclear factor-jB is known to control the inflammatory response in cells, and together with TNFa, monocyte chemoattractant protein (MCP)-1, and IL-6 was found to be upregulated in P15 T17M retinas. 3 To determine if Csp-12 ablation in P30 T17M retinas elevates NF-jB signaling in response to, as an example, microbial infection and thus causes photoreceptor cell death, we analyzed the levels of NF-jB (p65). We were interested in NF-jB in particular because NFjB-promoted signaling has been shown to be activated in the Csp-12 À/À mouse experimental model of colonic inflammation.…”
Section: Csp-12 Ablation In T17m Retinas Significantly Modifies Exprementioning
confidence: 99%
“…1,2 The study of molecular mechanisms underlying the retinopathy in these mice has demonstrated that the unfolded protein response (UPR), along with inflammatory signaling, significantly contributes to the progression of retinal degeneration. 3 Thus, the activation of all three UPR branches, including protein kinase R-like endoplasmic reticulum kinase (PERK), activating transcriptional factor 6 (ATF6), and inositol-requiring enzyme 1 (IRE1), has been detected in T17M retinas as early as postnatal (P) day 15. Moreover, we have recently revealed that the rate of retinal degeneration could be significantly altered in these mice by modifying the expression of UPR hallmark proteins.…”
mentioning
confidence: 99%